2004
DOI: 10.1007/s00022-004-1659-9
|View full text |Cite
|
Sign up to set email alerts
|

An angle in Minkowski space

Abstract: A new angular measure in Minkowski space is introduced. It is defined for a cone of any dimension, is additive and invariant under invertible linear transformations. For the dimension 2, it has a clear interpretation as an "amount of rotation" in the Minkowski space from a direction to another one. (2000): Primary 51B20, 52A38. Mathematics Subject Classification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Dekster [1] also showed that if : M 1 → M 2 is a linear transformation from a twodimensional Minkowski space M 1 into another two-dimensional Minkowski space M 2 such that the unit disk B 1 of M 1 is mapped onto the unit disk B 2 of M 2 , then 1. for any α < β, M 1 (α, β) = M 2 ( (α, β)), where (α, β) denotes the cone (sector) whose edges are the images of the rays R α and R β .…”
Section: We Havementioning
confidence: 99%
See 1 more Smart Citation
“…Dekster [1] also showed that if : M 1 → M 2 is a linear transformation from a twodimensional Minkowski space M 1 into another two-dimensional Minkowski space M 2 such that the unit disk B 1 of M 1 is mapped onto the unit disk B 2 of M 2 , then 1. for any α < β, M 1 (α, β) = M 2 ( (α, β)), where (α, β) denotes the cone (sector) whose edges are the images of the rays R α and R β .…”
Section: We Havementioning
confidence: 99%
“…In [1], Dekster calculated the total angle measure τ = (0, 2π) around a point for several Minkowski spaces M. Specifically,…”
Section: We Havementioning
confidence: 99%
“…A new angular measure for cones of any dimensions in d-dimensional Minkowksi space M d was introduced recently [1]. When the cone is also d-dimensional, one can introduce naturally the total angular measure τ d around a point in M d , see [1, 3.7].…”
Section: Introductionmentioning
confidence: 99%
“…Let w(ϕ) be the width of B 2 in the direction ϕ + π/2. According to [3], (3.1.1), the Minkowski angle in M 2 between α and β equals…”
mentioning
confidence: 99%
“…We are going to use Theorem 1.2 in[3] (on invariance of the angular measure) to show that the sums (2.3.2) and (2.6.7) have equal addends:…”
mentioning
confidence: 99%